2018
DOI: 10.1021/acs.inorgchem.8b00304
|View full text |Cite
|
Sign up to set email alerts
|

Preferential Adsorption of CO2 in an Ultramicroporous MOF with Cavities Lined by Basic Groups and Open-Metal Sites

Abstract: Here, we present a new ultramicroporous Cu paddlewheel based MOF. This ultramicroporous MOF has most of the features such as porosity (BET surface area = 945 m/g), CO capacity (3.5 mmol/g at ambient temperature and pressure), CO/N selectivity (sCO/N = 250), and fast CO diffusion kinetics ( D = 2.25 × 10 m/s), comparable to some of the other high-performing ultramicroporous MOFs, with strong binding sites. Typically, such MOFs exhibit strong CO-framework interactions (evidenced from a heat of adsorption ≥ 38 kJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 48 publications
4
25
0
Order By: Relevance
“…MOF material lined by basic amine groups and the high CO2 uptake was not accompanied by strong adsorbent-adsorbate interactions. 45 It appears that, at the degree of functionalization we achieve, IEA does not change significantly. Invoking acidbase properties also does not help in interpreting the observation: the heterocyclic nitrogen atoms in NA (pKa 4.…”
Section: Co2 Capture Performancementioning
confidence: 82%
“…MOF material lined by basic amine groups and the high CO2 uptake was not accompanied by strong adsorbent-adsorbate interactions. 45 It appears that, at the degree of functionalization we achieve, IEA does not change significantly. Invoking acidbase properties also does not help in interpreting the observation: the heterocyclic nitrogen atoms in NA (pKa 4.…”
Section: Co2 Capture Performancementioning
confidence: 82%
“…Interestingly, its uptake of CO 2 is higher or comparable with other amine or amino acid based system (Table S1, ESI †). 12,19 On the other hand, the uptake of CH 4 is less compared to CO 2 at 298 K, 273 K, and 263 K, which are 15.1 cm 3 g À1 , 21.2 cm 3 g À1 , and 24.8 cm 3 g À1 , respectively (Fig. 4d).…”
Section: Gas and Vapor Sorption Studymentioning
confidence: 96%
“…These Q st values have been compared with other MOFs (Table S1, ESI †). Interestingly, Zn-CBS shows comparable and higher Q st for CO 2 than MIL-53(Cr) (32 kJ mol À1 ), 20 IRMOF-9-NMe 2 (27 kJ mol À1 ), 21 TEA@bio-MOF-1 (26.5 kJ mol À1 ), 22 CPF-13 (28.3 kJ mol À1 ), 14 JUC-141 (27.85 kJ mol À1 ), 10 IISERP-MOF20 (26 kJ mol À1 ), 12 [Zn(atz) 2 ] (26 kJ mol À1 ), 16 [Zn 2 (BDC) 2 (DABCO)] (25 kJ mol À1 ), 23 NOTT-202a (22 kJ mol À1 ), 24 [Zn 4 (OH) 2 (1,2,4-BTC) 2 ] (20 kJ mol À1 ), 25 and IRMOF-3 (19 kJ mol À1 ). 26 Whereas, the Q st for methane is higher than those reported for the MOFs in the literature, such as, SNU-100 (26.5 kJ mol À1 ), 16 JUC-141 (22.7 kJ mol À1 ), 10 [Zn(atz) 2 ] (19.5 kJ mol À1 ), 16 IITKGP-6 (18.4 kJ mol À1 ), 29 SNU-151 (18.2 kJ mol À1 ), 41 IITKGP-5 (14.8 kJ mol À1 ), 15 SNU-77S (14.3 kJ mol À1 ), 41 and SNU-150 (12.8 kJ mol À1 ).…”
Section: Gas and Vapor Sorption Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The orientation of CO 2 molecules in the pores of MOFs was found effective to alter the interaction with guest CO 2 . Nandi et al [198] . revealed that the CO 2 molecules align parallel to the open metal sites of Cu‐MOF and get sandwiched between two open metal sites by GCMC simulations (Figure 19a).…”
Section: Metal–organic Frameworkmentioning
confidence: 98%